Status of a Person with Mental Disorders in Administrative Law Regulations - Żukowski, Lech J. (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The text attempts to describe the issue of the status of a person with mental disorders, which is acquired under the norms of administrative law through an appropriate administrative procedure. This status has the features of the so-called formal status due to procedural issues. The possession by a person of (at least) one of two groups of presented judgments. The possibility of specifying the concept of the formal status of a person with mental disorders significantly increases the scope of protection of basic values for administrative law, which include health, life and human dignity. In order to achieve the assumed goals, the study uses the dogmatic and legal methodology.